The Influence of Safety, Occupational Health (K3), and Work Discipline on Employee Performance Construction Project PT. Sasak Indo Raya - Hasanah, Sholehatul; Fuady, CA Helmy; Yuniarti, Titi (The Eastasouth Management and Business, 2024)
This research aims to assess the impact of safety, health, and work discipline on the performance of construction workers. This study employed quantitative methodologies with a sample size of 34 individuals. This research demonstrates that work safety (X1) significantly impacts employee performance on construction projects at PT. Sasak Indo Raya. The significance value of the work safety variable (X1) is 0.001, which is less than 0.05 (0.001 < 2.032). The occupational health variable (X2) significantly influences employee performance on construction projects at PT. Sasak Indo Raya. The significance value of the occupational health variable (X2) is 0.035, which is less than 0.05 (0.035 < 2.032). The work discipline variable (X3) significantly influences employee performance at PT. Sasak Indo Raya. The significance value of the Work Discipline variable (X3) is 0.000, which is less than 0.05 (0.000 < 2.032).